1998
DOI: 10.1088/0268-1242/13/10/024
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a high-performance InGaAsP/InP integrated laser with butt-coupled passive waveguides utilizing reactive ion etching

Abstract: We obtained high-performance 1.3 µm InGaAsP/InP buried heterostructure lasers integrated with butt-coupled waveguides using reactive ion etching (RIE) for mesa definition, brief chemical cleaning for damage relief and low-pressure metalorganic vapour phase epitaxy for the epitaxial layer growth. We measured a coupling efficiency between the active layer and the passive waveguide layer of over 91 ± 1.6% per facet across a quarter of a 2 inch InP wafer. The threshold current and the slope efficiency were 13 mA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Butt-joint is one of the technologies of fabricating DBR lasers. Wet chemical etching [10] , reactive-ion-etching (RIE) followed by HBr-based solution, [11] and RIE followed by selective wet etching [12] are three methods reported on the fabrication of these butt-coupled optical devices. For the lasers in the spectrum range of 1.6-1.9 μm, an InGaAs quantum-well material is often employed, which is a little different from that within the 1.35-1.5 μm range with InGaAsP material.…”
mentioning
confidence: 99%
“…Butt-joint is one of the technologies of fabricating DBR lasers. Wet chemical etching [10] , reactive-ion-etching (RIE) followed by HBr-based solution, [11] and RIE followed by selective wet etching [12] are three methods reported on the fabrication of these butt-coupled optical devices. For the lasers in the spectrum range of 1.6-1.9 μm, an InGaAs quantum-well material is often employed, which is a little different from that within the 1.35-1.5 μm range with InGaAsP material.…”
mentioning
confidence: 99%
“…This design, however, suffers from an unacceptably large coupling loss of -5-6 dB at each active-passive junction [2]. We have demonstrated that using a lateral taper on the active waveguide drastically reduces the coupling loss and elevates the performance of TG-integrated devices to the level previously only possible using complicated epitaxial regrowth processes [3].…”
Section: Introductionmentioning
confidence: 97%